The Effectiveness of Discovery Blended Learning on Concept Understanding and Student Motivation - Tyas Nur Wijiastuti; Sri Nurhayati (Publindo Akademika, 2021)
This study aims to determine the effectiveness of discovery blended learning towards understanding concepts and learning motivation in the material of class VIII human excretion system in SMP Negeri 27 Semarang. This research is an experimental study with a true experimental design type posttest only control group design. Sampling was done by purposive sampling, with each experimental group and the control class. Data was collected using tests, observation sheets, and questionnaire sheets. The results showed that discovery blended learning was effective against the understanding of concepts and learning motivation of VIII grade students in SMP Negeri 27 Semarang which was seen from the percentage of conceptual understanding between the experimental class and the control class, there were significant differences between the average value of the experimental class concept understanding and the control class and the average learning motivation of the experimental classDiscovery Blended Learning, Concept Understanding, Learning Motivation